Synthesis and Characterization of Yttrium-Doped Hydroxyapatite Nanoparticles and Their Potential Antimicrobial Activity - Albulym, Obaid; Kaygili, Omer; Hussien, Mai S. A.; Zahran, H. Y.; Kilany, Mona; Darwish, R.; Yahia, I. S. (Amer Scientific Publishers, 2021)
This study reports a detailed analysis of the yttrium doping effects into hydroxyapatite (HAp) nano-structures at different amounts (e.g., 0, 1, 2.5, 5, 7.5, 10, and 15%) on the structural, spectroscopic, dielectric, and antimicrobial properties. For this purpose, seven HAp samples having the Y-contents mentioned above were prepared using the microwave-assisted sol-gel precipitation technique. The structure of synthesized samples was fully described via X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transforms infrared (FTIR). Raman spectroscopy and dielectric measurements were used to characterize the spectroscopic properties. Furthermore, the samples' antimicrobial features have been assisted through the agar disk diffusion technique. This study showed that the crystallinity decreased with the adding of Y-ions inside the HAp matrix. The Y-contents have influenced the crystallite size, lattice parameters, dislocation density, lattice strain, and unit cell volume. The surface morphology is composed of the agglomerated smaller particles. Remarkable changes in the dielectric properties were observed with the adding of Y-ions. The alternating current conductivity obeys the Jonscher's relation. Y-doped hydroxyapatite nanoparticles have a considerable inhibitory effect against bacteria and fungi (Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Candida albicans). The Y-doped hydroxyapatite nanoparticles are a promising material for bone cement engineering with a potential bio-activity.
Keywords: Nanostructured Hydroxyapatite; Yttrium-Doped Hydroxyapatite; Dielectric Properties; FT-Raman/FTIR Spectroscopy; Antimicrobial Properties